2014
DOI: 10.1002/wcs.1323
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry

Abstract: The authors have declared no conflicts of interest for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
286
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(303 citation statements)
references
References 136 publications
13
286
1
3
Order By: Relevance
“…Measurement of pupil diameter, commonly used in the cognitive psychology literature (Sirois and Brisson, 2014) and used to assess effects of hearing loss on cognitive load (e.g., Zekveld et al, 2014), has also recently been used to investigate mental fatigue. Hopstaken et al (2014, 2015) suggest variations in pupil diameter are indicative of task engagement, a process which may be reduced in a fatigued state.…”
Section: Measuring Fatigue and Energymentioning
confidence: 99%
“…Measurement of pupil diameter, commonly used in the cognitive psychology literature (Sirois and Brisson, 2014) and used to assess effects of hearing loss on cognitive load (e.g., Zekveld et al, 2014), has also recently been used to investigate mental fatigue. Hopstaken et al (2014, 2015) suggest variations in pupil diameter are indicative of task engagement, a process which may be reduced in a fatigued state.…”
Section: Measuring Fatigue and Energymentioning
confidence: 99%
“…New technology affords researchers with non-invasive physiological measures of cognitive effort during speech or visual perception (Sirois and Brisson 2014). In particular, pupillometry provides a reliable measure of responses to visual stimuli and it is generally accepted that relative changes in pupil size reflect systematic changes in cognitive exertion (De Gelder and Vroomen 2000; Massaro and Egan 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pupil size, which reflects activity in the sub-cortical locus coeruleus attention system, fluctuates as an adaptive response to both changes in the environment as well as changes in cognitive task load (Laeng, Sirois, and Gredebäck 2012). There is evidence that pupils dilate in difficult processing environments, such as when translating difficult words or processing syntactic ambiguities (Engelhardt, Ferreira, and Patsenko 2010; Hyönä, Tommola, and Alaja 1995; Sirois and Brisson 2014). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Mental effort, as described above, is easily measured. As numerous studies have shown, the pupil faithfully dilates when observers engage in a task that in some way requires mental effort (for recent reviews, see Laeng, Sirois, & Gredebäck, 2012;Sirois & Brisson, 2014; for a classic, but remarkably insightful review, see Loewenfeld, 1958): The seminal studies by Kahneman and Beatty (1966) have shown that the pupil dilates as a result of increased working memory load; pupil dilation indicates the amount of effort invested in speech comprehension (Zekveld, Kramer, & Festen, 2010); more recently, and more directly related to the present study, it has been shown that pupillary dilation accompanies the detection of a target in a rapid serial visual presentation paradigm (Privitera, Renninger, Carney, Klein, & Aguilar, 2010; see also Wolff, Scholz, Akyurek, & Rijn, 2015), and that pupil size indicates search difficulty in visual search (Porter, Troscianko, & Gilchrist, 2007) and multiple-object tracking (Alnaes et al, 2014).…”
mentioning
confidence: 99%